Benchmarking the Stability of Oxygen Evolution Reaction Catalysts: The Importance of Monitoring Mass Losses. Issue 12 (5th October 2014) - Frydendal, Rasmus; Paoli, Elisa A.; Knudsen, Brian P.; Wickman, Björn; Malacrida, Paolo; Stephens, Ifan E. L.; Chorkendorff, Ib
Abstract Because of the rising need for energy storage, potentially facilitated by electrolyzers, improvements to the catalysis of the oxygen evolution reaction (OER) become increasingly relevant. Standardized protocols have been developed for determining critical figures of merit, such as the electrochemical surface area, mass activity and specific activity. Even so, when new and more active catalysts are reported, the catalyst stability tends to play a minor role. In this work, we monitor corrosion on RuO2 and MnOx by combining the electrochemical quartz crystal microbalance (EQCM) with inductively coupled plasma mass spectrometry (ICP–MS). We show that a meaningful estimation of the stability cannot be achieved based on purely electrochemical tests. On the catalysts tested, the anodic dissolution current was four orders of magnitude lower than the total current. We propose that even if long‐term testing cannot be replaced, a useful evaluation of the stability can be achieved with short‐term tests by using EQCM or ICP–MS.